Measurement of charm production at central rapidity in proton-proton collisions at √s=7 TeV - Abelev, B.; Abrahantes Quintana, A.; Adamova, D.; Adare, A. M.; Aggarwal, M. M.; Rinella, G. Aglieri; Agocs, A. G.; Agostinelli, A.; Aguilar Salazar, S.; Ahammed, Z.; Ahmad, N.; Masoodi, A. Ahmad; et al. (SPRINGER, 2012)
The p(t)-differential inclusive production cross sections of the prompt charmed mesons D-0, D+, and D*(+) in the rapidity range vertical bar y vertical bar K-pi(+), D+ -> K-pi(+)pi(+), D*(+) -> D-0 pi(+), and their charge conjugates, about 8,400 D-0, 2,900 D+, and 2,600 D*(+) mesons with 1 < p(t) < 24 GeV/c were counted, after selection cuts, in a data sample of 3.14 x 10(8) events collected with a minimum-bias trigger (integrated luminosity L-int = 5 nb(-1)). The results are described within uncertainties by predictions based on perturbative QCD.
Keywords: Hadron-Hadron Scattering; PRODUCTION CROSS-SECTIONS; P(P)OVER-BAR COLLISIONS; ART.; PROMPT; MESON; QCD; PP; Physics